Financial resources, eco-innovation and sustainability performance in automotive industry - Maldonado-Guzmán, Gonzalo (2022)
Eco-innovation is considered in the literature as one of the most important constructs that substantially improve the environmental sustainability of manufacturing companies. However, it has been shown that companies alone cannot adequately develop eco-innovation activities, to achieve not only a higher level of eco-innovation activities, but also a significant improvement in the level of sustainable performance of manufacturing firms. In addition, little is known about the relationship between financial resources, eco-innovation and sustainable performance fill this gap in the literature and explore the relationship between these three main constructs through an extensive review of the literature. Likewise, a self-administered questionnaire was distributed to a sample of 460 through confirmatory factor analysis and structural equation models. The results obtained suggest that financial resources have significant positive effects on eco-innovation, and eco-innovation has significant positive effects on the sustainable performance of firms in the automotive industry